Investigación y desarrollo conceptual de sistema de aerobombeo para aplicaciones agrícolas (2020)
The correct irrigation of agricultural crops is a fundamental factor to assure the success of the harvests. It varies depending on the type of crop. In most cases, irrigation of crops depends on rainwater that is affected by climatic phenomena, which generates variations in the seasons and the water resources. By not having the necessary amount of water, the crops do not germinate, causing economic losses. This study seeks to propose a windpump system for a range of specific conditions such as type of crop, water source, wind speed, geographic conditions, and type of irrigation, in order to increase the wind energy obtained focused on the design of the runner. An environmental study was implemented evaluating the conditions of the municipality, then different pumping equipment were dimensioned, and a commercial study was carried out to determine the most effective. Subsequently, modifications to the design were proposed and the irrigation method was conceptualized. It was found that, for the environmental conditions of the municipality of Samacá, Boyacá, wind pumping is a viable option to correctly irrigate the bulb onion crops. The efficiency of the equipment improves 17.85 % with the increase of the area swept by the rotor. Finally, it is recommended to validate the theoretical results with an experimental study and to publish the study to implement the results in crops for the Samacá region for future research.